[Atmospheric concentration of fungus spores in Ankara and the effect of meteorological factors in 2003 period]. - Ceter, Talip; Pinar, Nur Münevver (My University, 2010)
The atmospheric concentrations of airborne fungus spores change continuously according to the meteorological factors, and their intensity have important allergic effects on atopic subjects and opportunistic pathogenic effects on immunocompromised patients. The aim of this study was to identify the fungal spores found in Ankara atmosphere during 2003 period and to investigate the changes in spore concentrations in relation to meteorological factors. Fungal spores were sampled by using 7-day Burkard volumetric trap between January to December 2003, and probable identification was performed microscopically based on their morphological structures. A total of 433.079 spores/m3 belonging to 35 taxa were observed during the study. The rates of these taxa were as follows; 75.5% Cladosporium, 6.1% Alternaria, 2.2% Leptosphaeria, 2.2% Ustilago, 2.1% 1-septate ascospores, 2% Exosporium, 1.6% Pleospora, and 1.3% Drechslera. The other taxa with concentrations < 1% have consisted a total of 7.1% of all atmospheric spores (Puccinia, Curvularia, Coprinus, Nigrospora, Periconia, Melanomma, Torula, Ascobolus, Agrocybe, Pithomyces, Stemphyllium, Ganoderma, Boletus, Peronospora, Venturia, Paraphaeosphaeria, Epicoccum, Didymella, Chaetomium and Fusarium rates between 0.7-0.1%; Oidium, Xylaria, Botrytis, Melanospora, Dictyosporium, Sporormiella and Tetracoccosporium rates between 0.09-0.01%). Although fungal spores were detected in all months in Ankara atmosphere, the evaluation of the seasonal distribution of spore concentrations revealed that the highest value was detected in July (100.697 spores/m3), while the lowest value was in January (4268 spores/m3). When the effects of meteorological factors on spore concentrations were investigated, it was found that, monthly mean temperature (> 20 degrees C) has a strong positive correlation (p < 0.01), and monthly mean relative humidity (< %50) and precipitation (0-20 mm) have strong negative correlations (p < 0.01) on the spore concentrations, while wind velocity (3 m/s) has a slightly positive effect. An annual spore calendar which indicated weekly concentrations and allergenicity levels of those identified fungal spores, was also prepared in this study. In conclusion, it is expected that these data would be helpful for the researchers in the area of aeropalinology and for the clinicians to evaluate allergic diseases.
Keywords: Turkey; Rain; Air Microbiology; Temperature; Humidity; Wind; Opportunistic Infections; Spores, Fungal; Immunocompromised Host; Hypersensitivity; Humans; Seasons; Weather; 13. Climate action